Relações de trabalho e sua precarização: uma crítica à terceirização - Silva, Gabriela Mendes (2018)
The research portrays the application of business organization models in outsourced work relations and their effects that persist in the present time. It addresses the historical process of struggle between capital and labor, in order to foster economic development without suppressing worker protection. In this context, the impacts of globalization arising from the process of industrialization in labor relations are highlighted, analyzing the decent work approach issued by the International Labor Organization, based on international legal instruments applicable from the point of view of the rights humans. Specific points of Law 6.019/1974, as amended by Laws 13.429/2017 and 13.467/2017, regulate outsourcing in Brazil, as well as the understanding of the Supreme Courts (TST and STF) regarding the authorization of outsourcing in Brazil activity-order. The bilateral employment relationship is exploited as a socially protected constitutional right, without, however, failing to bring the outsourcing approach under the corporate bias, which advocates an increase in competitiveness and productivity based on free enterprise and freedom of contract. Finally, we present some hypotheses of precariousness of working conditions present in outsourcing: wage inequality, social unprotection due to high rates of industrial accidents, threatened trade union protection and the contractor's responsibility for the payment of labor claims in the workplace outsourcing.